The Doha Conference - Birth of a new trade round - Godel, Martin H. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Ministers of 142 countries and customs territories gathered in Doha, Qatar on 9-14 November 2001 for the 4th Ministerial Conference of the World Trade Organization (WTO). The objective was to set the agenda for a new trade round further liberalizing international trade and strengthening the multilateral trade-body.Two years ago in 1999 the delegates failed to agree on the launch of a new round at the 3rd Ministerial Conference of the WTO in Seattle, USA. The failure caused growing fear about the international community's ability to find consensus on multilateral economic policy matters and ultimately creating concern about the stability of the world economy's framework. However two years later WTO members could reach consensus on the agenda for a new trade round. Starting from this puzzling fact that countries could find agreement about issues they could not even discuss two years earlier, the Thesis intends to come up with reasons explaining the changes leading to such an outcome as well as carefully studying in details the negotiations in Doha. Before entering the subject, the methodology chosen shall be explained. The author uses the 'two-level game' framework to bring light in the paper's topic.